2010
DOI: 10.14742/ajet.1095
|View full text |Cite
|
Sign up to set email alerts
|

Faculty's acceptance of computer based technology: Cross-validation of an extended model

Abstract: The first aim of the present study is to validate an extended technology acceptance model (TAME) on the data derived from the faculty members of a university in an ongoing, computer mediated work setting. The study extended the original TAM model by including an intrinsic motivation component -computer self efficacy. In so doing, the study assessed the direct and indirect effects of computer self efficacy on the use of the technology, via the perceived usefulness and intention to use the technology voluntarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 36 publications
(40 reference statements)
8
65
1
5
Order By: Relevance
“…The study also seems to emphasise the general robustness of TAM, just as similar studies in other contexts have done (e.g. Park, 2009;Ahmad, Basha, Marzuki, Hisham & Sahari, 2010;Tarcan, Varol & Toker, 2010). Contextual differences are reflected in the performance enhancement factor.…”
Section: Research Findingssupporting
confidence: 67%
See 1 more Smart Citation
“…The study also seems to emphasise the general robustness of TAM, just as similar studies in other contexts have done (e.g. Park, 2009;Ahmad, Basha, Marzuki, Hisham & Sahari, 2010;Tarcan, Varol & Toker, 2010). Contextual differences are reflected in the performance enhancement factor.…”
Section: Research Findingssupporting
confidence: 67%
“…Park found that SN exerts a relatively strong influence on PU. Ahmad et al (2010) supported the findings with regard to SE, as their findings suggest that lecturers' computer self-efficacy has an important influence on both PU and UB. Tarcan et al (2010) introduced facilitating conditions (FC) as an additional construct encompassing the organisational conditions such as training, education and technical support that create the environment for technology acceptance (or non-acceptance).…”
Section: The Technology Acceptance Model (Tam) In Higher Educationsupporting
confidence: 65%
“…In the technology mediated learning environment, technology self-efficacy was also found to have significant impact on students' adoption and use of technologies and learning performance (e.g. Ahmad, Basha, Marzuki, Hisham & Sahari, 2010;Tsai, Tsai, & Hwang, 2010). If students feel uncomfortable with the technologies that they use in their learning and do not feel confident in their ability to use the technology effectively, they may experience difficulty in their interactions with peers and instructors, and in the completion of their work.…”
Section: Technology Self-efficacymentioning
confidence: 99%
“…Az utóbbi időben azonban egyre nagyobb népszerűségnek örvend az oktatási kutatások területén is (Leguina [2015]). Alkalmazzák például a tanulói vagy oktatói attitűd, a megítélés, a képesség vagy a szándék vizsgálatára (Ahmad et al [2010], Al-Gahtani [2016], Cheng [2013], De Smet et al [2012], Del Barrio-Romero-Frías-Arquero [2013], Najmul Islam [2013], Lee-Hsiao-Purnomo [2014], Sanchez-Franco [2010], Sánchez-Hueros [2010], van Raaij-Schepers [2008], Yang et al [2011]). …”
Section: Tárgyszóunclassified
“…A technológiaelfogadás témájú oktatási kutatásokban az egyik leggyakrabban alkalmazott moderátor változó a nem (Ahmad et al [2010] Egyesek szerint nincsenek nemi különbségek a TAM-változók közötti összefüggé-sek tekintetében (Ahmad et al [2010], Arenas-Gaitan-Rondan-Cataluna-RamirezCorrea, [2010]), míg mások szerint a PU és a PEU másként határozzák meg a technológia elfogadását, másként hatnak az A-ra, a viselkedésre a nők és a férfiak körében. Mivel a technológiahasználat általában könnyebb a férfiak számára, a férfiak biztosabbak a technológia használatában (Teo-Lim-Lai [1999]), így a PEU nem játszik olyan fontos szerepet a férfiaknál sem az A (Padilla et al [2013]), sem a technológia-használat (Kim [2010], Terzis-Economides [2011]) befolyásolásában, mint a nőknél.…”
Section: A Nemek Közötti Különbségekunclassified